Female God-Fearers in 1 Timothy - Adrian, Matthias ca. 20./21. Jh. (Judaica: neue digitale Folge, 2024)
In this paper, the role of the women addressed in the New Testament’s First Letter to Timothy is viewed in the context of ancient reciprocity, using the example of 1 Tim 2:8-15. By adopting the expression θεοσέβεια (piety) female assembly members are asked for their donations which were to be used for the community’s benefit while at the same time they are forbidden to teach there publicly. While θεοσέβεια is only mentioned here, an attitude of piety is characteristically rendered by εὐσέβεια in 1 Timothy as well as in the related letters (2 Timothy; Titus). According to Greco-Roman thought piety is accompanied by certain social duties such as giving benefactions to a community. While εὐσέβεια can designate an honorable attitude within the reference field of communal beneficence, the cognate expression θεοσέβεια is often used by Jewish communities to honor Gentile God-fearers for benefactions received. By employing θεοσέβεια in 1 Tim 2:10 with regard to women’s duties in the church, the author of the letter addresses women who match the profile of such wealthy female God-fearers. His double goal is to secure their benefactions to support the new male elite materially and at the same time contain the influence they exert through their teaching activities in the community.